Assessment Of Factors Affecting the Development of Tourist Zone Activities - Saydaliyeva Umidaxon Solijon qizi (Genius Journals, 2024)
This article describes the types of tourist areas, features of their development, factors influencing their development, determination of the economic efficiency of these factors, a program of measures to assess structural changes in factors and its stages.
Keywords: Tourist And Recreational Zone; Free Economic Zone; Factors Of Economic Efficiency